THE INTERNATIONAL STANDARDS AND THE KAZAKHSTAN LEGISLATION IN THE SPHERE OF SOCIAL RESPONSIBILITY OF BUSINESS - Aiymgul, Tleuzhanova; Elizaveta, Li; Kasymbekovna, Aktanova Aliya (European Scientific Journal, ESJ, 2015)
Today social responsibility of business is recognized the major making long-term strategy of a sustainable development of the country. In this regard the considerable attention is paid to advance of ideas of corporate social responsibility, creating favorable conditions for socially responsible behavior of the enterprises. In 2008 at the first Forum on social responsibility of business, the head of state Nursultan Nazarbayev set qualitatively new level of inclusion of business in the solution of major problems of development of society and in this regard charged to continue work on formation of the favorable environment stimulating increase by subjects of business of corporate social responsibility. Signing in 2008 of the Agreement between the Ministry of Labor and Social Protection of the population of RK and the large companies on advance of the principles of the Global contract of the UN in the sphere of the social and labor relations became the important instrument of development of social responsibility of business. For the first time business structures assumed obligations for observance of requirements of national laws, the principles of 12 ratified Conventions of the International Labor Organization (ILO) which are directed on freedom of association and recognition of the right for the conclusion of collective agreements, elimination of all forms of forced labor, including, child labor, elimination of discrimination in the sphere of work and employment. Today in Kazakhstan many elements of world practice of maintaining corporate social responsibility are used.